Bronchoalveolar Lavage Cell Immunophenotyping Facilitates Diagnosis of Lung Allograft Rejection - Greenland, J. R.; Jewell, N. P.; Gottschall, M.; Trivedi, N. N.; Kukreja, J.; Hays, S. R.; Singer, J. P.; Golden, J. A.; Caughey, G. H. (American journal of transplantation, 2014)
Supplementary methods to identify acute rejection and to distinguish rejection from infection may improve clinical outcomes for lung allograft recipients. We hypothesized that distinct bronchoalveolar lavage (BAL) cell profiles are associated with rejection and infection. We retrospectively compared 2939 BAL cell counts and immunophenotypes against concomitantly obtained transbronchial biopsies and microbiologic studies. We randomly assigned 317 subjects to a derivation or validation cohort. BAL samples were classified into four groups: infection, rejection grade ≥A1, both or neither. We employed generalized estimating equation and survival modeling to identify clinical predictors of rejection and infection. We found that CD25+ and natural killer cell percentages identified a twofold increased odds of rejection compared to either the infection or the neither infection nor rejection groups. Also, monocytes, lymphocytes and eosinophil percentages were independently associated with rejection. A four‐predictor scoring system had high negative predictive value (96–98%) for grade ≥A2 rejection, predicted future rejection in the validation cohort and predicted increased risk of bronchiolitis obliterans syndrome in otherwise benign samples. In conclusion, BAL cell immunophenotyping discriminates between infection and acute rejection and predicts future outcomes in lung transplant recipients. Although it cannot replace histopathology, immunophenotyping may be a clinically useful adjunct. Quantification of bronchoalveolar lavage cell types, including CD25+ and natural killer cells, can help discriminate between infection and acute rejection, predict future acute rejection, and predict bronchiolitis obliterans syndrome in lung transplant recipients. See editorial by Neujahr on page 748.